Literatur-Zensur- und Gegenstrategien. Die Fälle Johannes R. Becher und Heinrich Mann in der Weimarer Republik - Haupt, Jürgen (Wydawnictwo Naukowe UAM, 1995)
Starting out from H. Mann's public statements about the trials against J.R. Becher's ,,Levisite“ and Arthur Schnitzler's ,,Reigen“ Haupt interprets H. Mann's journalistic campaign against literary censorship in the Weimar Republic as well es his role in the section ,,Literary Art“ of the Prussian Academy of Arts as being the heroic illusion of a courageous man striving to enlighten the public in the face of the emergence of fascism.